A Comparison of Educational Interventions to Enhance Cultural Competency in Pharmacy Students - Sales, Ibrahim (American Journal of Pharmaceutical Education, 2013)
Objective. To determine the degree to which 3 different educational interventions enhance cultural competency in pharmacy students. Methods. Students were equally divided among a simulated-patient activity group, a written case-scenarios group, and a formal lecture group. Mean scores for pre- and post-intervention cultural self-assessment surveys were compared. Results. In the simulation group, there were significant positive changes in the cultural skills and cultural desire components; in the case-scenario group, there was a significant positive change in the cultural awareness component; and in the lecture group, there were significant positive changes in the cultural skills and cultural empathy components. With respect to the cultural skills component, there was greater post-intervention improvement in the simulation and lecture groups than in the case-scenario group. Conclusions. There were significant positive changes within each group, indicating that ideologies and behaviors may be altered based on the educational intervention received. However, a 1-hour practicum may not be sufficient to enhance cultural competency.